A novel validated method for predicting the risk of re-hospitalization for worsening heart failure and the effectiveness of the diuretic upgrading therapy with tolvaptan. - Hideyuki Takimura; Tasuku Hada; Mami Kawano; Takayuki Yabe; Yukako Takimura; Satoru Nishio; Masatsugu Nakano; Reiko Tsukahara; Toshiya Muramatsu (PLoS ONE, 2018)
Increased re-hospitalization due to acute decompensated heart failure (ADHF) is a modern issue in cardiology. The aim of this study was to investigate risk factors for re-hospitalization due to worsening heart failure, and the effect of tolvaptan (TLV) on decreasing the number of re-hospitalizations. This was a multicenter, retrospective study. The re-hospitalization factors for 1191 patients with ADHF were investigated; patients receiving continuous administration of TLV when they were discharged from the hospital (n = 194) were analyzed separately. Patients were classified into 5 risk groups based on their calculated Preventing Re-hospitalization with TOLvaptan (Pretol) score. The total number of patients re-hospitalized due to worsening heart failure up to one year after discharge from the hospital was 285 (23.9%). Age ≥80 years, duration since discharge from the hospital after previous heart failure <6 months, diabetes mellitus, hemoglobin <10 g/dl, uric acid >7.2 mg/dl, left ventricular ejection fraction (LVEF) <40%, left atrial volume index (LAVI) >44.7 ml/m2, loop diuretic dose ≥20 mg/day, hematocrit <31.6%, and estimated glomerular filtration rate (eGFR) <50 ml/min/1.73m2 were independent risk factors for re-hospitalization for worsening heart failure. There was a significant reduction in the re-hospitalization rate among TLV treated patients in the Risk 3 group and above. In conclusions, age, duration since previous heart failure, diabetes mellitus, hemoglobin, uric acid, LVEF, LAVI, loop diuretic dose, hematocrit, and eGFR were all independent risk factors for re-hospitalization for worsening heart failure. Long-term administration of TLV significantly decreases the rate of re-hospitalization for worsening heart failure in patients with a Pretol score of 7.